2018
DOI: 10.1039/c8ra00157j
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stoichiometry on the structural, thermal and electronic properties of thermally decomposed nickel oxide

Abstract: A thermal decomposition route with different sintering temperatures was employed to prepare non-stoichiometric nickel oxide (Ni1−δO) from Ni(NO3)2·6H2O as a precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(89 citation statements)
references
References 41 publications
6
82
0
1
Order By: Relevance
“…The lattice parameters and unit cell volume of the pure samples are also listed in Table 1 , showing good agreement with those published in the literature. 27 , 33 35 However, an increase in the cell volume and lattice parameters was observed when compared with ICSD no. 14000 30 and no.…”
Section: Resultsmentioning
confidence: 89%
“…The lattice parameters and unit cell volume of the pure samples are also listed in Table 1 , showing good agreement with those published in the literature. 27 , 33 35 However, an increase in the cell volume and lattice parameters was observed when compared with ICSD no. 14000 30 and no.…”
Section: Resultsmentioning
confidence: 89%
“…In figure 5(b), the Ni 2p core level spectrum consists of satellite and two sublevel peaks of Ni 2p 3/2 and Ni 2p 1/2 occurred by spin-orbit splitting. The sublevel peaks are contained with six deconvoluted peaks (Ni 1-Ni 6), which was assigned to Ni 2+ and Ni 3+ [26][27][28]. The O 1s core level spectrum of NiO film was resolved into five peaks (O 1-O 5) as shown in figure 5(c).…”
Section: Resultsmentioning
confidence: 99%
“…5 a–e, it was found that the Ni 2p core level spectra of 0 M, 0.05 M, 0.1 M, 0.15 M and 0.2 M Co-NiO films consist of satellite and sublevel peaks of Ni 2p 3/2 and Ni 2p 1/2 . These sublevel peaks were resolved into six peaks (Ni 1 to Ni 6), which Ni 1, Ni 2, Ni 4 and Ni 5 peaks were assigned to Ni 2+ and the remaining peaks (Ni 3 and Ni 6) were registered to Ni 3+ 33 , 34 . The Ni 1 to Ni 6 peaks of 0 M, 0.05 M, 0.1 M, 0.15 M and 0.2 M Co-NiO films have a similar location but their intensity is different because the number of Ni 3+ and Ni 2+ ions in each condition is not equal, depending on Co concentration.…”
Section: Resultsmentioning
confidence: 99%